Legal Protection for Workers for Late Payment of Wages: The Principles of Justice Perspective - Arnis Setiani Isma; Sakka Pati; Marwah Marwah (Institut Agama Islam Negeri (IAIN) Kendari, 2022)
This article intends to analyze and review employment agreements that protect workers from late wage payments and oversight of labor engagement over late wage payments for workers. This research is normative juridical research. Legal materials used primary, secondary, and tertiary legal materials. The findings showed that the realization of the principle of justice in working relationships is created through the rights and obligations of the parties to mutual reciprocity (balanced). It contained in the employment agreement, including the imposition of fines as sanctions to avoid arbitrariness on the part of employers. The involvement of labor supervision must be optimal to realize the working relationship by the principle of justice. This research implied that it is mandatory by law in a work bond to enter into a collective agreement as a form of accountability between the entrepreneur and the workforce. It is to protect the rights of each party.